2020
DOI: 10.1002/humu.24014
|View full text |Cite
|
Sign up to set email alerts
|

Functional characterization of four ATP‐binding cassette transporter A3 gene (ABCA3) variants

Abstract: ABCA3 transports phospholipids across lamellar body membranes in pulmonary alveolar type II cells and is required for surfactant assembly. Rare, biallelic, pathogenic ABCA3 variants result in lethal neonatal respiratory distress syndrome and childhood interstitial lung disease. Qualitative functional characterization of ABCA3 missense variants suggests two pathogenic classes: disrupted intracellular trafficking (type I mutant) or impaired ATPase‐mediated phospholipid transport into the lamellar bodies (type II… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(21 citation statements)
references
References 40 publications
(122 reference statements)
5
16
0
Order By: Relevance
“…If the acidic property at this position is well conserved in the ABCA1-A4 subgroup, this is less evident in the second subgroup, to which ABCA3 belongs. Bioinformatics tools all supported a pathogenic effect, consistent with previous in vitro studies which showed partially impaired lipid transport and smaller lamellar bodies [ 23 , 24 ]. This mutation was associated with variable phenotype in homozygous patients, in infants with severe respiratory distress syndrome as well as in an adult with idiopathic pulmonary fibrosis [ 3 , 25 ].…”
Section: Discussionsupporting
confidence: 85%
“…If the acidic property at this position is well conserved in the ABCA1-A4 subgroup, this is less evident in the second subgroup, to which ABCA3 belongs. Bioinformatics tools all supported a pathogenic effect, consistent with previous in vitro studies which showed partially impaired lipid transport and smaller lamellar bodies [ 23 , 24 ]. This mutation was associated with variable phenotype in homozygous patients, in infants with severe respiratory distress syndrome as well as in an adult with idiopathic pulmonary fibrosis [ 3 , 25 ].…”
Section: Discussionsupporting
confidence: 85%
“…of the different cell lines. We assessed IB, fluorescence-based colocalization, and vesicle ultrastructure of the A549/ABCA3 2/2 cells that stably express individual ABCA3 variants and the adenoviral transduced A549 and ATII cells, as previously described (14,19) (see data supplement). We also assessed vesicle diameter and liposome uptake of the A549/ABCA3 Corrector rescue.…”
Section: Methods Of Functional Characterizationmentioning
confidence: 99%
“…ABCA3 undergoes N-terminal cleavage from a primary translation product to a post-translationally modified product in the multivesicular bodies (34). Mistrafficked ABCA3 proteins that are retained in the endoplasmic reticulum fail to undergo this cleavage, and only the primary translation product is detected (1,(13)(14)(15)(16)(17)(18)(19). IB of mistrafficked ABCA3 mutant proteins demonstrates a single, uncleaved 220-kD band that results from the sum of mobilities of ABCA3 protein (190 kD) and mCherry or GFP (z30 kD).…”
Section: Abca3 Protein Processingmentioning
confidence: 99%
See 2 more Smart Citations